Underwater Sound Levels in Glacier Bay During Reduced Vessel Traffic Due to the COVID-19 Pandemic - Gabriele, Christine M.; Ponirakis, Dimitri W.; Klinck, Holger (Frontiers in Marine Science, 2021)
The global COVID-19 pandemic caused a sharp decline in vessel traffic in many areas around the world, including vessel-based tourism throughout Alaska, USA in 2020. Marine vessel traffic has long been known to affect the underwater acoustic environment with direct and indirect effects on marine ecological processes. Glacier Bay National Park in southeastern Alaska has monitored underwater sound since 2000. We used continuous, calibrated hydrophone recordings to examine 2020 ambient sound levels compared with previous years: 2018, the most recent year with data available, and 2016 for historical perspective. Park tourism occurs mainly in May–September. Overall, the number of vessel entries in Glacier Bay was 44–49% lower in 2020 (2020: n = 1,831; 2018: n = 3,599; 2016: n = 3,212) affecting all vessel classes, including the complete absence of cruise ships and only three tour vessel trips. In all years, we found clear seasonal and diurnal patterns in vessel generated noise, focused from 06:00 to 20:00 local time (LT) in the summer months. Broadband (17.8–8,910 Hz) sound levels in the 2020 Visitor Season were 2.7 dB lower than 2018 and 2.5 dB lower than 2016. Focusing on morning (06:00–09:00 LT) and afternoon (15:00–18:00 LT) time-blocks when tour vessels and cruise ships enter and exit Glacier Bay, median broadband sound levels were 3.3–5.1 dB lower in 2020 than prior years. At the 95th percentile levels, morning and afternoon peak times in 2020 were 6.3–9.0 dB quieter than previous years. A 3 dB decline in median sound level in the 125 Hz one-third octave band in 2020 reflects a change in medium and large vessel noise energy and/or harbor seal vocalizations. Our results suggest that all types of vessels had a role in the quieter underwater sound environment in 2020, with the combined acoustic footprint of tour vessels and cruise ships most evident in the decrease in the 95th percentile loudest sounds. This and other descriptions of the pandemic-induced quiet, and the gradual return to increased activity, can help inform efforts to improve existing methods to mitigate vessel noise impacts and maintain the ecological integrity of marine protected areas.